Level of digital competencies in students of Information and Communication Technologies (ICT) at an Ecuadorian university - Rentería Macías, Henry (2024)
The present research consists of an exploratory study on student digital competencies. The objective is to analyze the level in its five areas: information, communication, content creation, security and problem solving, in students of the subject 'Computer Projects' of the ninth cycle of the systems engineering career of the Technical University "Luis Vargas Torres" of Esmeraldas. The research had a quantitative approach, with a non-experimental design and two intact groups. As an instrument, a test called "Ikanos", for testing digital competencies of universal character and validated in university students in Europe and Latin America. The results showed that the two groups are not equivalent and have an Intermediate level. This indicated that, despite being students of the ICT career, they could not be placed mostly in Advanced and Expert level. It is concluded about the need to include the development of digital competence as a fundamental element throughout the academic curriculum, from the beginning of the career of Information and Communication Technologies of UTLVTE, implementing strategies, from the first academic cycle, in the career.